The interplay of configuration and conformation in helical perylenequinones: Insights from chirality induction in liquid crystals and calculations - Frezza, Elisa; Pieraccini, Silvia; Mazzini, Stefania; Ferrarini, Alberta; Spada, Gian Piero (Beilstein Journal of Organic Chemistry, 2012)
The chirality transfer in liquid crystals induced by two helical perylenequinones (namely, the natural compounds cercosporin and phleichrome) was investigated by integrating measurements of helical twisting power with a conformational analysis by DFT calculations and with the prediction of their twisting ability by the surface-chirality method. The two quasi-enantiomeric derivatives induce oppositely handed cholesteric phases when introduced as dopants in nematic solvents. We evaluated the role of the different conformations of the chiral hydroxyalkyl side chains in determining the helical twisting power: They were found to affect the strength of the chirality transfer, although the handedness of the induced cholesteric phase is essentially determined by the axial chirality (helicity) of the core of the perylenequinones.
Keywords: chirality; conformational analysis; DFT calculations; helical twisting power; nematic liquid crystals